Toward multiscale consequential sustainable process design: Including the effects of economy and resource constraints with application to green urea production in a watershed. (2nd November 2019) - Lee, Kyuha; Ghosh, Tapajyoti; Bakshi, Bhavik R.
Highlights: The RCOT-P2P multiscale technology choice modeling framework is developed. The framework integrates process engineering, life cycle, and economy models. Market constraints are considered as a consequential approach. The framework is applied to the green urea production in the watershed. Results demonstrate how designs from the conventional approach can be misleading. Abstract: Decisions made by approaches that only consider the environmental domain could result in unexpected outcomes due to burdens shifting to economic and social domains. These consequences could occur through the entire supply chain at multiple spatial scales. In this work, the process-to-planet (P2P) multiscale modeling framework is integrated with the rectangular choice-of-technology (RCOT) consequential approach. The resulting RCOT-P2P multiscale technology choice modeling framework takes account of market effects, such as economic resource constraints, as a consequential approach for designing engineering systems and their supply chain networks. The integrated modeling framework can represent different stakeholders' interests by considering engineering, environmental, and economic dimensions. The case study focuses on installation of a new green urea production system in a watershed where there are limited supplies of resources, such as water and land area. We identify how the adoption of new technologies could change and be limited by market constraints, as the urea demand increases. This multiscale consequential framework is useful for modeling substitution effects of emerging technologies while considering market effects.